Regression Model as a Tool for Evaluating Mangrove Degradation in Lembar Bay, West Lombok - Johari, Harry Irawan; Rahmat, Nurul Isnaeni; Sukuryadi, Sukuryadi (Universitas Muhammadiyah Mataram, 2025)
The mangrove ecosystem plays a vital role in maintaining ecological balance, supporting economic livelihoods, and sustaining socio-cultural functions. However, in Lembar Bay, West Lombok Regency, this ecosystem is increasingly threatened by human activities, particularly land conversion for aquaculture. These activities have led to significant ecological degradation, biodiversity loss, and weakened coastal protection. This study aims to analyze the key factors influencing mangrove degradation and to evaluate the effectiveness of regression models in assessing the contribution of these factors. A quantitative research approach was employed, with data collected through structured questionnaires distributed to 45 purposively selected community members considered knowledgeable about local mangrove conditions. The study also integrated field measurements and satellite imagery interpretation to assess mangrove density, biodiversity, and related environmental variables. Multiple linear regression analysis was used to examine the relationship between anthropogenic pressures such as land clearing, water quality, and rehabilitation efforts and indicators of mangrove degradation, namely biodiversity and mangrove density. Regression analysis showed a strong and significant effect of water quality on both mangrove biodiversity and density. The biodiversity regression model produced a correlation coefficient (R) of 0.820 and a determination coefficient (R²) of 0.673, indicating that 67.3% of the variation in biodiversity can be explained by the analyzed factors. Similarly, the mangrove density model yielded an R of 0.800 and R² of 0.640, meaning that 64.0% of the variation in mangrove density was explained. F-test results confirmed that both models were statistically significant (p-value < 0.05). The findings indicate that aquaculture expansion and land use changes are the most critical contributors to mangrove degradation. These pressures directly impair the physical condition of the ecosystem, leading to biodiversity loss and increased vulnerability to coastal hazards. Based on community perceptions, most respondents supported stricter sanctions against mangrove destruction and agreed that mangrove conservation improves the quality of life. Therefore, this study recommends that policymakers and local governments strengthen their roles in monitoring and controlling land use changes, enforcing environmental regulations, and promoting environmental education programs. It is also essential to enhance community participation in mangrove rehabilitation through inclusive, knowledge-based initiatives and integrate scientific evidence into participatory coastal spatial planning. This study contributes to the scientific literature on mangrove conservation by demonstrating the empirical effectiveness of regression analysis in identifying and quantifying human-induced pressures affecting mangrove ecosystems.